Services Infrastructure Forming in the Process of Transport Logistics Stock Movement - Bogoviz, Aleksei V.; Ragulina, Yulia V.; Lobova, Svetlana V.; Zhukov, Boris M.; Stepanova, Olga M. (International Review of Management and Marketing, 2016)
Logistics as a scientific and practical direction, covering a wide range of business activities, has gained a strong position in the world economic system. As a priority has proved the concept of integrated logistics, based on the consolidation of the participants of freight and goods movement system to ensure continuity and regularity of material products and associated information, service and financial flows in the intra, regional, inter-regional, sectoral and international levels. The experience of the developed capitalist countries shows that the use of logistics systems is to reduce transport costs by 7-20%. The costs of handling and storage of material resources and finished products are reduced by 15-30%; total logistics costs to 12-35%. Accelerated turnover of material resources by 20-40%. Reserves and resources of finished goods reduced by 50-100%. In short, the game is worth the candle. The formation of market relations in Russia urgently requires the formation of transport and logistics infrastructure. Its fundamental, system-elements should be hubs, main and local railways, container and working with products terminals, multimodal transport and logistics centers (MTLTS). In large network-wide units of federal and international level, such as Moscow, Leningrad (St. Petersburg), Krasnodar and others. Target-consistent creation of a network of regional terminals and logistic centers, Union-United in regional integrated transport and logistics system. Keywords: mobile service system, transport logistics, transport hubs JEL Classifications: L14, L17, L23, M11